1983
DOI: 10.1002/ajh.2830150303
|View full text |Cite
|
Sign up to set email alerts
|

Glycophorin a expression in malignant hematopoiesis

Abstract: Two hundred twenty-nine patients with hematopoietic malignancies were tested for reactivity with a monoclonal anti-human glycophorin A antibody. One hundred twenty-three of these cases were classified as acute leukemias of either the myeloid, lymphoid, erythroid, or undifferentiated type. The monoclonal antibody we used (VIE-G4) was obtained after immunization with a human thymocyte suspension. It selectively reacts with glycophorin A (GpA) and strongly binds to 40% of K-562 cells and all morphologically recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The large OKIapositive cells might be Kupffer cells, myeloid or megakaryocyte precursors, or large pre-B cells (Natali et al, 1987). In addition, erythroid progenitor cells negative to MAb against glycophorin A might also belong to this OKIa-positive population (Liszka et al, 1983). The small cells positive for HLA-DR are more likely to be mature lymphoid cells, as previously described (Kamps and Cooper, 1982).…”
Section: Non Lineage-specific Hemopoiesismentioning
confidence: 76%
“…The large OKIapositive cells might be Kupffer cells, myeloid or megakaryocyte precursors, or large pre-B cells (Natali et al, 1987). In addition, erythroid progenitor cells negative to MAb against glycophorin A might also belong to this OKIa-positive population (Liszka et al, 1983). The small cells positive for HLA-DR are more likely to be mature lymphoid cells, as previously described (Kamps and Cooper, 1982).…”
Section: Non Lineage-specific Hemopoiesismentioning
confidence: 76%
“…The R10 antibody reacts with an epitope in the middle part of the polypeptide chain, the R18 antibody reacts with a region close to the lipid bilayer (21), and the VIE-G4 antibody needs sialic acid for reactivity (22 contributes to the conformation of the antigenic determinants of GPA.…”
Section: Discussionmentioning
confidence: 99%
“…Using monoclonal antibodies to GPA for the phenotyping of leukemic cells, only occasional reactivity is found (22,42). This discrepancy might be explained by the differentiation-related structural changes in GPA.…”
Section: Discussionmentioning
confidence: 99%
“…Second, these data suggest that iden tification of erythroleukemia should probably be per formed using a panel of antibodies against various epi topes on several different'glycophorin species. Previous workers have shown that monoclonal antibodies directed against the M and N determinants of sialoglycoproteins a and § bind only to late erythrocyte precursors [36], and that antibodies which depend on carbohydrate-depen dent epitopes of a are unreliable in detecting erythroleu kemia [37], Thus, antibody E5 may prove to be a more reliable probe for erythroleukemia than antibodies di rected against a.…”
Section: Discussionmentioning
confidence: 99%